1987
DOI: 10.22237/elephant/1521732102
|View full text |Cite
|
Sign up to set email alerts
|

Mount Elgon's Elephants Are in Peril

Abstract: The elephants at Mount Elgon National Park (MENP) are unique and exceptional. They are the only elephants known to excavate for salt in underground caves. Data on the ecology of elephants at MENP were collected over a period of seven years with a total of 130 days of field observations. Methods employed included: direct observations, spoor, photographs, and sound recording. Elephants visited the caves singly or in groups of up to 19 individuals; visits lasted up to 6 hours in Kitum and Makingeny Caves. Most vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…) ;南アフリカの チャクマヒヒ (Gow, 1973) ;アフリカ西部の セ ネ ガ ル の サ バ ン ナ チ ン パ ン ジ ー Pan troglodytes (Pruetz, 2007) と チ ャ ク マ ヒ ヒ Papio papio (McGrew et al, 2003) ;ケニア西部 エルゴン山のキトゥム洞窟 Kitum Cave での 3 種の霊長類 (アヌビスヒヒ Papio anubis, ブルー モンキー Cercopithecus mitis,アビシニアコロ ブ ス Colobus guereza) (Redmond & Shoshani, 1987) ; ベ ト ナ ム の デ ラ ク ー ル ラ ン グ ー ル Trachypithecus delacouri (Rogers, 2002) ; 中 国 南部の広西壮(チワン)族自治区のシロアタ マ ク ロ リ ー フ モ ン キ ー Trachypithecus leucocephalus (Huang et al, 2003) ;中国南部の 貴 州 省 の フ ラ ン ソ ワ ル ト ン Trachypithecus francoisi (Grueter & Wei, 2006 Here we report the intensive use of caves by Japanese macaques (Macaca fuscata) in a heavy snow fall area (Kurobe Gorge, eastern Toyama Prefecture) in central Japan based on the occurrence of abundant feces found within the Saru-ana Cave (a limestone cave). The Kanetsuri area where this study was conducted is located along the middle reaches of Kurobe Gorge, and is one of the heavy snow fall areas in Japan, where snowfall cover ranges in depth from 2 to 3 meters in winter.…”
unclassified
“…) ;南アフリカの チャクマヒヒ (Gow, 1973) ;アフリカ西部の セ ネ ガ ル の サ バ ン ナ チ ン パ ン ジ ー Pan troglodytes (Pruetz, 2007) と チ ャ ク マ ヒ ヒ Papio papio (McGrew et al, 2003) ;ケニア西部 エルゴン山のキトゥム洞窟 Kitum Cave での 3 種の霊長類 (アヌビスヒヒ Papio anubis, ブルー モンキー Cercopithecus mitis,アビシニアコロ ブ ス Colobus guereza) (Redmond & Shoshani, 1987) ; ベ ト ナ ム の デ ラ ク ー ル ラ ン グ ー ル Trachypithecus delacouri (Rogers, 2002) ; 中 国 南部の広西壮(チワン)族自治区のシロアタ マ ク ロ リ ー フ モ ン キ ー Trachypithecus leucocephalus (Huang et al, 2003) ;中国南部の 貴 州 省 の フ ラ ン ソ ワ ル ト ン Trachypithecus francoisi (Grueter & Wei, 2006 Here we report the intensive use of caves by Japanese macaques (Macaca fuscata) in a heavy snow fall area (Kurobe Gorge, eastern Toyama Prefecture) in central Japan based on the occurrence of abundant feces found within the Saru-ana Cave (a limestone cave). The Kanetsuri area where this study was conducted is located along the middle reaches of Kurobe Gorge, and is one of the heavy snow fall areas in Japan, where snowfall cover ranges in depth from 2 to 3 meters in winter.…”
unclassified
“…It was noted that many caves seem to have multiple names, and that names given in previous literature may not correspond with caves of the same name today. Location coordinates are not supplied in the literature, and the only survey published is a rudimentary one of Kitum Cave (Sutcliffe, 1973, in which the cave is misnamed; Redmond and Shoshani, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…In many cases, the collapse is very recent, the slabs on the floor being only slightly fractured and all the fracture surfaces still fresh and unweathered. The most recent collapse in the Kitum Cave main chamber is known to have occurred in 1982, when a large section fell, killing at least one elephant (Redmond and Shoshani, 1987). Exploration of the less accessible parts of the caves, beyond the collapse blocks and under the deep undercuts of the extremities, revealed that the base of most of the cave walls (at least those not obscured by collapse) is in the green clay unit.…”
Section: The Cavesmentioning
confidence: 99%
See 2 more Smart Citations